ENHANCING CRITICAL THINKING THROUGH MATHEMATICAL HABITS OF MIND AND GEOGEBRA ON THE PYTHAGOREAN THEOREM - Edy Supratman; Akhsanul In'am; Dyah Worowirastri Ekowati (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2025)
This study was conducted in response to the low level of students' critical thinking skills and the predominance of teacher-centered instruction in mathematics classrooms. It aims to analyze the differences in students' critical thinking skills between those taught using the MHM approach assisted by GeoGebra and those taught through traditional methods on the topic of the Pythagorean Theorem in Class VIII at SMPN 3 Lingsar, West Lombok.Â  This study employed a quasi-experimental design, specifically a nonequivalent control group design, involving two groups of 27 students each.Â  The experimental group received instruction using the MHM approach with GeoGebra, which emphasizes reflective, persistent, and evidence-based mathematical thinking habits, while the control group used conventional methodsÂ  Data were collected through pretest and posttest critical thinking assessments, student worksheets, and learning observations. The initial abilities of both groups were comparable, as indicated by the independent t-test on the pretest (p > 0.05). Posttest results showed a significant improvement in the experimental group (mean = 82) compared to the control group (mean = 65), with a posttest p-value of 0.000 (< 0.05) and a very large effect size (Cohen’s d = 1.90), indicating a substantial difference in learning outcomes between the groups.Â  Observations also revealed very high engagement levels in the experimental group. These findings demonstrate that the MHM approach, aided by GeoGebra, effectively enhances students' critical thinking skills and fosters reflective, systematic, and collaborative learning habits. This study recommends adopting MHM strategies and visual technologies like GeoGebra in mathematics education.